2013
DOI: 10.1002/jcb.24596
|View full text |Cite
|
Sign up to set email alerts
|

COMP-Ang1 accelerates chondrocyte maturation by decreasing HO-1 expression

Abstract: Endochondral ossification is essential for new bone formation and remodeling during the distraction stage. Endochondral ossification is attributed to chondrocyte maturation, which is induced by various factors, such as the cellular environment, gene transcription, and growth factor expression. Cartilage oligomeric matrix protein (COMP)-angiopoietin 1 (Ang1) is more soluble, stable, and potent than endogenous Ang1, and COMP-Ang1 treatment has osteogenic and angiogenic effects in an in vivo model of bone fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Enhancing the expression of antioxidant enzymes in articular chondrocytes is a potential therapeutic approach in OA (Cai et al, 2015; Koike et al, 2015; Takada et al, 2015). The expression of HO-1, a key mediator of antioxidant defense, decreases with aging in articular cartilage and menisci of mouse knees (Takada et al, 2015) , and decreased HO-1 accelerates chondrocyte hypertrophic differentiation and Runx2 expression (Kim et al, 2013). On the other hand, the constitutive expression of HO-1 in mouse chondrocytes and meniscus reduces severity of joint damage with aging (Ochiai et al, 2008; Takada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing the expression of antioxidant enzymes in articular chondrocytes is a potential therapeutic approach in OA (Cai et al, 2015; Koike et al, 2015; Takada et al, 2015). The expression of HO-1, a key mediator of antioxidant defense, decreases with aging in articular cartilage and menisci of mouse knees (Takada et al, 2015) , and decreased HO-1 accelerates chondrocyte hypertrophic differentiation and Runx2 expression (Kim et al, 2013). On the other hand, the constitutive expression of HO-1 in mouse chondrocytes and meniscus reduces severity of joint damage with aging (Ochiai et al, 2008; Takada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression pattern of VEGF and Ang-1 in antler cartilage, we conjectured that they might play a similar role of promoting new blood vessel invasion into cartilage and keeping chondrocytes survival. Meanwhile, Ang-1 might activate Tie-2 which was also highly expressed in antler chondrocytes, and further stimulate blood vessel invasion into hypertrophic zone of cartilage (Jing et al 2013 ; Kim et al 2013 ). On the contrary, Ang-2 was a naturally occurring antagonist of Ang-1 and could competitively inhibit Ang-1-induced activation of Tie-2 (Escobar et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ang is involved in the maturation, stabilization and remodeling of vessels (Toyama et al 2009 ). Four members of the Ang family have been discovered and the best studied are angiopoietin-1 (Ang-1) and Ang-2 which regulate the angiogenesis in the process of endochondral ossification and participate in cartilage vascularization and chondrocyte maturation (Jing et al 2013 ; Kim et al 2013 ). Ang-1 and Ang-2 exert their biological effects through activating or blocking the activation of their receptor tyrosine kinase with immunoglobulin and epidermal growth factor homology domains (Tie-2).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of metal ions is considered, together with other factors, responsible for the high failure rates of MoM big head hip devices. In a number of studies, the presence of these ions was associated with the induction of oxidative stress (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that Co (II) dose-and time-dependently induces HMOX-1 expression in different cell lines (33,40). In addition, in vivo studies that demonstrated HMOX-1 induction by Co, were conducted predominantly in the seventies and eighties (36)(37)(38), while the most recent studies were conducted in animal models (32,34,35,39). In these studies Cr appears to exhibit a different role on HMOX-1, depending on whether it is in the Cr (III) or Cr (VI) form.…”
Section: Discussionmentioning
confidence: 99%